Collaborative mind mapping in RICOSRE learning model to improve students’ information literacy - Liah Badriah; Susriyati Mahanal; Betty Lukiati; Murni Sapta Sari (International Journal of Evaluation and Research in Education (IJERE), 2024)
This research aimed to determine how the reading, identifying problem, constructing solution, solving problem, reviewing and extending problem solution (RICOSRE) learning model integration with collaborative mind mapping affects students’ information literacy in higher education institutions. This quasi-experimental study used a pretest-posttest non-equivalent control group design. There were 40 multiple-choice questions selected to assess student information literacy. All instruments have been validated and are reliable. The data were collected from 100 participants who were college students enrolled in the environmental pollution course of the biology education degree program at Siliwangi University, Indonesia. To analyze the research data, analysis of covariance (ANCOVA) was used at a 5% level of significance, followed by the least significance difference (LSD) test. The ANCOVA results showed that the RICOSRE-CMM learning model impacted students’ information literacy. LSD scores were significantly different in terms of students’ information literacy. It can be concluded that the RICOSRE-CMM model could enhance each component of information literacy as these components have been integrated into the learning model syntax, which involves a series of information discovery and analysis processes during group work to find a solution to a problem.